Forecasting the liquidity of very small private companies - Mramor, Dusan; Valentincic, Aljosa (Journal of Business Venturing, 2003)
Short-term liquidity of very small private companies (VSPCs) is important to creditors as any cash shortages result in opportunity costs due to delayed payments. We use a publicly available liquidity indicator for 19,627 Slovenian VSPCs as a special, but generalizable case of “credit record” data and financial ratios to predict possible cash shortages. Indicator is predicted and used in lagged form(s) as a predictive variable with/without financial ratios, allowing comparisons. Models, including financial ratios, are less efficient than models based on lagged liquidity indicator alone. Surprisingly, combined models perform only marginally better. Despite high overall accuracy, misclassification of companies experiencing cash shortages is high.